"We'll Accept Anything, as Long as She Is Okay": Italian Parents' Narratives of Their Transgender Children's Coming-out. Issue 5 (20th October 2021) - Frigerio, Alessandra; Montali, Lorenzo; Anzani, Annalisa; Prunas, Antonio
Abstract: The aim of the study was to explore the experiences and representations of Italian parents of TGE (Transgender and Gender-Expansive) adolescents diagnosed with gender dysphoria who, for the first time, attended a gender clinic for psychological consultation. This study presents findings from fifteen parents of TGE adolescents, mostly (93%) trans boys, aged 14–19. The analysis identified four main themes: Gender Dysphoria: Something Impossible to Understand, Resigned Acceptance, Strategies of social acceptance in a complex context and The Limits of Healthcare Services . Results are discussed in the light of a highly transphobic social and cultural context.